2021
DOI: 10.2185/jrm.2021-016
|View full text |Cite
|
Sign up to set email alerts
|

The utility of physician-staffed helicopters for managing individuals who experience severe isolated head trauma

Abstract: Objective: The authors retrospectively investigated prognostic factors for severe isolated head trauma in patients evacuated by a physician-staffed helicopter emergency medical service (HEMS) or ground ambulance using data from the Japan Trauma Data Bank (JTDB). Patients and Methods: This study was a retrospective analysis of data housed in the JTDB database. The study period was from January 2004 to May 2019. Subjects were divided into two groups according to the method of transportation: helicopter (i.e., HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… 32 , 33 , 34 , 35 In contrast, some observational studies in Japan indicated that compared to ground ambulances, the helicopter system was not associated with survival in patients with severe burns, isolated severe head trauma, or pediatric patients with severe head trauma. 36 , 37 , 38 It may be because the helicopter system cannot provide an early definitive treatment to resolve time-critical conditions.…”
Section: The Physician-staffed Helicopter System In Japanmentioning
confidence: 99%
“… 32 , 33 , 34 , 35 In contrast, some observational studies in Japan indicated that compared to ground ambulances, the helicopter system was not associated with survival in patients with severe burns, isolated severe head trauma, or pediatric patients with severe head trauma. 36 , 37 , 38 It may be because the helicopter system cannot provide an early definitive treatment to resolve time-critical conditions.…”
Section: The Physician-staffed Helicopter System In Japanmentioning
confidence: 99%
“…A previous study also demonstrated that the DH was not identified as a significant predictor of survival for patients with severe head injuries in comparison to patients transported by ground ambulances when utilizing the Japan Trauma Data Bank. [ 2 ]…”
mentioning
confidence: 99%